Familial clustering of autoimmune diseases in patients with type 1 diabetes mellitus (2006)
We investigated the familial aggregation of autoimmune diseases (AIDs) among first-degree relatives (FDR) of patients with type 1 diabetes mellitus (T1D). Relatives of 98 T1D patients defined according to the guidelines diagnosis of the American Diabetes Association and 113 matched controls without any AID, were interviewed using a questionnaire that sought information about demographic and medical characteristics including a list of 18 AIDs. Genetic analysis was performed using the program ASSOC and by calculating recurrent risk ratios. In cases, 25.5% of the families had at least one member having an AID, while in controls there were 9% (odds ratio [OR]: 3.96, 95% confidence interval [CI] = 1.74-9.0, p = 0.0006). An AID was registered in 8.3% of 312 FDR of patients as compared with 2.4% of 362 FDR in controls (OR: 3.56, 95% CI = 1.64-7.73, p = 0.0008). The most frequent AIDs registered in FDR of cases were autoimmune thyroid disease (AITD) and T1D, which disclosed coefficients of aggregation. These results indicate that AIDs cluster within families of T1D patients adding further evidence to consider that clinically different autoimmune phenotypes may share common susceptibility gene variants, which may act pleiotropically as risk factors for autoimmunity. © 2006 Elsevier Ltd. All rights reserved.